The Effectiveness of Using Lectora Based on Aceh Culture on Linear Equation System Material - Fadilah Fadilah; Rizki Amalia; Roni Priyanda (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aim of this study to analyze the effectiveness of using Lectora based on Aceh culture on Linear Equation System Material. This research uses a quantitative descriptive research approach. The research design used was the One Group Pretest-Posttest Design. The conclusions of this study are as follows: 1) the results of the observation of the teacher's ability in managing learning were 83.92% with good categories; 2) the results of observations of student activities during the learning process were quite active with a percentage of 73.08%; 3) The results of the percentage of student response questionnaires were 51.67%, which means that most students responded well to the use of Aceh culture-based lectora media on the material of linear equation systems; 4) Statistical test with t test obtained t count = 30,11865 and t table = 1,729133 (  = 0,05), t count > t table means that the use of media is effectively used; and 5) Aceh Culture-Based Lectora Media is effectively used in learning linear equation systems. The results of the overall data analysis indicate that the use of Aceh Culture-Based Lectora is effective for student learning outcomes on linear equation material.